Catholic fundamentalism: towards a discussion of the phenomenon and the application of the term - Dmitriy Golovushkin (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2025)
The article is devoted to the topic of catholic fundamentalism, which is not sufficiently highlighted in Russian church-historical science. It aims to update the discussion on the possibility of the religious phenomenon Catholic Fundamentalism, as well as to address the question of the admissibility of using the concept of “catholic Fundamentalism” in relation to catholic conservatism and restorationism of the 20th century. The article analyses the discursive space of the phenomenon of catholic fundamentalism, which lies within the boundaries of “fundamentalism – traditionalism – integrationism-integrationism’, reveals the theoretical and methodological problems of conceptualizing catholic fundamentalism, and solves the problem of defining its “generic features”. In general, the article offers methodological tools and ways of rethinking the more than half a century-long debate on the question of whether catholic integrationism-integrism and catholic traditionalism are specific forms of religious fundamentalism. It significantly expands the understanding of the variability of confessional forms of religious fundamentalism, especially in the discourse on its “foundations”.